PENGARUH PROMOTIONAL MIX TERHADAP PENINGKATAN JUMLAH PASIEN LVR (LASER VAGINA REJUVENATION) DI RUMAH SAKIT HAPPY LAND MEDICAL CENTRE YOGYAKARTA - Dwi Suharyanta (STIKes Surya Global Yogyakarta, 2016)
Background: Technological advances and competition in the field of higher health business make direction of hospital to offer the best service treatment and make an active movement promotion. Promotional mix is a part of marketing but promotion that can be done by hospital is limited by a law in Indonesia and the arrangement of hospital, and product innovation becomes an important part, and Happyland Medical Centre issue of product innovation it is LVR (laser vagina rejuvenation) and problems in this research is the influence of promotional mix to increase the number of patients LVRObjectives: this research is to know the influence promotional mix with a simultant there is or not.Methods.This research is associatif research with cross sectional technic. Population of this research are total of visiting of obstetric care patient in a last year is 38 peoples with a fullsample 38 peoples and use nonprobability sampling with accidental sampling, technics of gathering data is use observation, interview and questioner.The Result: Analysis data use the validity and reliability analysis, this research also use the multiple regression analysis, t test and f test. From the result of this research can be known: Y= 32,246 + 0,117 X1 + 0,245 X2 + 0,307 X3 + 0,315 X4 + 0,324 X5 + e. And value of significant is 0,0040,05 so (p)α. F value is 0,05 so influence the dependent variable with a simultant because F count F table (9,083 2,51). where as determinant coefficient (R2) is 0,327.The conclution: of this research is the influence of promotional mix to increase the number of patients LVR of Happy Land Medical Centre about 32,7 % and we wish that the hospital managerial will be use the promotional mix to introduce LVR Product to large prospect and apply cast media, leafleat etc, in promotional mix.Keyword: Increase the number of patients LVR, Promotional mix